Conservação de cereais de inverno com o uso de aditivos microbianos - Becker, Eduardo Garcia (2019)
In order to evaluate the productivity, nutritional composition and fermentative parameters in winter, oat and wheat cereal silages, in different conservation forms, associated or not with homo and heterofermentative inoculants, an experiment was conducted in the central region of Rio Grande do Sul, Brazil. The work was conducted during two years, in the harvests of 2015 and 2016 where sowing and cutting were carried out during the months of June to October, respectively. The cutt were performed in flowering stage and pasty to farinaceous grain to make the pre-dried silage and silage, respectively. In the harvest of 2015, treatments with one genotype of oats (cv. Guapa) and two of wheat (cv. BRS Umbu and cv. TBIO Energia I) were used, where each genotype was submitted to a control group in the form of silage without addition of the inoculant (SSI) and two groups with different levels of addition of a bacterial inoculant (S1X and S2X) TotalSilo®. In the 2016 crop, two wheat cultivars (TBIO Energy I and II) and a mixture of both cultivars submitted to three forms of conservation, silage without inoculant, silage with inoculant and pre-dried silage were used. In both experiments, after sixty days of storage, the silos were opened and homogeneous samples were taken for analysis of pH, N-NH3 and buffering power. Evaluations of the bromatological composition and productivity of the cereals studied were carried out. PH reduction was observed with the use of the bacterial inoculant in oat and wheat cultivars. The levels of NDFcp and ADFcp were lower with the bacterial inoculant, and higher for TDN and NFC. Therefore, it obtained a higher estimate of dry matter consumption. When we evaluated the conservation forms, the silage presented greater nutritive value, independent of the use of the inoculant in relation to the pre-dried silage. The TBIO I wheat presented a better chemical composition considering the reduction in the levels of NDFcp and ADFcp, and increases in CP, TDN, NFC and in the estimation of the relative value of the food. Productivity was higher for oats in relation to wheat cultivars, however there was a higher production of CP and TDN per hectare for wheat genotype TBIO I in relation to oats and UMBU wheat. The addition of the bacterial inoculant improved the fermentation process, and the wheat genotype TBIO I presented better chemical composition in relation to the other winter cereals studied. The conservation of cereals as silage presented a better fermentation pattern and higher chemical composition in relation to pre-dried silage.